250 SEA-TGT is a nonfucosylated antibody with distinct and amplified effector function activity that leverages the dependencies of anti-TIGIT anti-tumor activity upon Fc? R engagement. (9th November 2020) - Smith, Alyson; Zeng, Weiping; Siegall, William; Grogan, Bryan; Haass, Jane; Blackmarr, Amber; Thurman, Robert; Peterson, Scott; Gardai, Shyra
Abstract : Background: TIGIT is an immunoregulatory receptor expressed on activated and memory T cells, T regulatory cells (Tregs), and NK cells. TIGIT binding to CD155 and CD112 on tumor cells drives an inhibitory signal resulting in decreased T cell functionality. TIGIT targeting has been reported to release these inhibitory signals, drive Treg depletion, augment CD8 T cell generation, and promote anti-tumor responses. Methods: To evaluate the impact of antibody backbone on anti-TIGIT action three distinct antibodies with differential backbone effector functions, wild type, Fc(gamma)R null (LALA), and Fc(gamma)R enhanced (nonfucosylated, SEA-TGT), were incorporated onto a human anti-TIGIT antibody and assessed. The nonfucosylated SEA-TGT backbone was distinct from the LALA and wild type backbone through increased binding to activating FcyRIIIa receptor while concomitantly decreasing binding to the inhibitory Fc(gamma)RIIb receptor. Results: Independent of backbone all TIGIT antibodies blocked ligand binding and restored CD226 signaling. The effector null backbone neither mediated Treg depletion nor naïve or memory CD8 T cell activation. However, the effector enhanced SEA-TGT significantly increased Treg depletion and activation of CD8 T cells over the comparator wild type anti-TIGIT antibody. The enhanced SEA-TGT also induced innate cell activation not seen with the other backbones. These in vitro results translated to curative in vivo anti-tumor activity in multiple syngeneic models as a single agent. Again, the effector null antibody was inactive in all models whereas the effector enhanced SEA-TGT drove curative responses beyond those seen with the standard wild type backbone. Increased activity correlated with a slight decrease in intra-tumoral Tregs and increases in CD8 memory T cells and innate cell activations. Anti-tumor response was associated with generation of long-term, antigen-specific immunity that resulted in complete tumor rejection upon tumor re-challenge. Conclusions: Collectively, these data indicate that modulation of CD8 T cell functionality is not solely through alterations in the TIGIT/CD226 signaling axis and that our nonfucosylated Fc?R enhanced antibody uniquely activates both adaptive and innate arms of the immune system for maximal CD8 T cell responses. They also underscore the anti-tumor therapeutic potential of a nonfucosylated TIGIT targeting antibody (SEA-TGT) as a monotherapy agent and in combination with PD(L)1 agents. We have initiated a phase 1 trial testing the safety and activity of SEA-TGT in patients with advanced solid tumors and select lymphomas (NCT04254107 ). Trial Registration: NCT04254107 Ethics Approval: Animals studies were approved by and conducted in accordance with Seattle Genetics Institutional Care and Use Committee protocol #SGE-029.